How Multiple Representations Develop Higher-Order Thinking Skills in Primary Mathematics Learning: An Experimental Study - Evi Faujiah; Risky Dwiprabowo; Budiono Budiono; Arhamuddin Ali (S&Co Publishing, 2026)
The development of Higher-Order Thinking Skills (HOTS) is one of the main focuses of 21st-century education, especially in mathematics learning that demands reasoning, problem-solving, and conceptual understanding. This study aims to analyze the effect of Multiple Representations (MR) on students' HOTS in elementary school mathematics learning, especially on fractions. The study used a quasi-experimental design with a non-equivalent control group design. Participants consisted of an experimental group (n = 25) who received Multiple Representations-based learning and a control group (n = 25) who received conventional learning. Data were collected using a HOTS test based on the revised Bloom's taxonomy, which includes indicators of analyzing (C4), evaluating (C5), and creating (C6) by containing verbal, visual, symbolic, and contextual representations. The results showed that the experimental group experienced a higher increase than the control group, with an average score increasing from 57.76 to 72.80, while the control group increased from 57.08 to 61.48. The results of the hypothesis testing showed a significant difference between the two groups (p < 0.05). These findings indicate that Multiple Representations are effective in improving HOTS through strengthening conceptual understanding, translation between representations, and developing analytical skills, evaluation, and the creation of mathematical solutions.